First, catch : study of a spring meal - Eagle, Thom (Grove Press, 2020)
"A literary tour de force, First, Catch is food writing at its best: a cookbook without recipes, an invitation to journey through the digressive mind of a chef at work, and a hymn to a singular nine-dish festive spring lunch. London chef Thom Eagle is an enthusiastic explorer of the world of ingredients and a thoughtful commentator on the ways immigration, technology, and fashion have changed the way we eat. He has the sharp eye of a food scientist, as he tries to identify the seventeen unique steps of boiling water, and the curious mind of a culinary historian, as he ponders what the spice silphium tasted like to the Romans, who ate it to worldwide extinction. Eagle is also a food philosopher, asking the question: at what stage does cooking begin? Is it when we gather and arrange what we will cook-and perhaps start to salivate? Or does it start even earlier, in the fleeting late-morning thought, "What should I eat for lunch?" Irreverent and charming, beautifully illustrated and brilliantly researched, First, Catch is perfect armchair cooking, for readers of Nigel Slater, Alice Waters, or Samin Nosrat, encouraging us to slow down and focus on what it means to cook and offering us inspiration to savor, both in and out of the kitchen"--